THE INFLUENCE OF WORK CULTURE, WORK MOTIVATION, TRAINING, AND HUMAN RESOURCE DEVELOPMENT ON IMPROVING WORK ETHIC - Ludiyanto, Alfian (Dynamic Management Journal, 2024)
This research aims to determine the influence of work culture variables on increasing work ethic, the influence of work motivation variables on increasing work ethic, the influence of training variables on increasing work ethic, and the influence of human resource development variables on increasing work ethic (Case Study of Coffee Farmers in Sumber Canting Village, District (Bottleinggo, Bondowoso Regency). This research uses a quantitative approach, which means research that aims to determine the influence or relationship between two or more variables. This research examines the influence of work culture, work motivation, training, and      HR development on increasing work ethic, using quantitative descriptive methods, namely to determine whether or not there is an influence of work culture, work motivation, training, and HR development on increasing work ethic. The results of this research can be partially concluded that work culture, work motivation, training, and human resource development have a significant effect on increasing work ethic.